Application of soil mulches on establishment and growth of native and commercial tall fescue (Festuca arundinacea Schreb.) in an arid environment - F. Kazemi; M. Jozay; F. Salahshoor; H. Farhadi (Desert, 2021)
Creating sustainable landscapes especially in arid climates is a significant challenge. To achieve sustainable landscapes, some strategies such as using native plants and soil mulches have been suggested. This study aimed to examine the quality and growth response of the native tall fescue (Festuca arundinacea Schreb.) compared with the corresponding commercial cultivar (Festuca arundinacea ‘Jaguar’) under different planting mulches in their planting and early growth stage in arid climate Mashhad city located in the northeast of Iran. Seeds of commercial cultivar and native species of Festuca arundinacea were sown in a sandy loam texture soil and four mulch treatments including vermicompost, leaf compost, cow manure and sand as control, were applied to cover the seeds. The result showed that the native species had greener color and narrower leaves compared to the commercial cultivar but its other NTEP (National Turfgrass Evaluation Program) traits including density, uniformity, establishment, softness of grass surface, quality after clipping, and total quality was lower than that in the commercial cultivar. Using vermicompost as the planting mulch (top dressing or cover mulch at the time of planting of the turfgrass) significantly improved all of the traits in the native species. Vermicompost increased the percentage of grass coverage, clipping dry weight, and the plant height and decreased the leaf width of plants and number and percentage of weeds. Utilizing native species of tall fescue with vermicompost as the planting mulch can promise as quality lawn as their commercial cultivar for native urban landscaping in Iran.